Responsible Business and Corporate Performance of Private Placements Firms - Abbas, Yasir Abdullah; Al-Frijawy, Jawad; Alrobaie, Ahmed Ismaeel Khedhair; Al-Jazaeri, Mohammed Basim Mohammed; Sabti, Yousif Mousa (South Asian Journal of Social Sciences and Humanities, 2023)
The purpose of this paper is to determine the impact of the quality of responsible business (RB) on the corporate performance (CP) of private placements firms (PPF) in Malaysia as a developing market. This study uses secondary data derived from the content analysis of the Datastream and annual reports of 145 sampled PPF listed on Bursa Malaysia for the period of 2008–2018 and employs the OLS and WLS regressions. The findings illustration that there is a positive and negative link between RB and its dimensions with CP. In particular, there is a negative and important link among the RB dimensions of employee and product with CP. Meanwhile, the general public and energy dimensions were found to have a positive and significant relationship with CP. This study tests the effect of the responsible business on the CP. Most studies on RB in Malaysia are conducted on public listed companies. To the researchers’ best knowledge, this study makes a significant contribution in terms of RB in PPF companies.